2012
DOI: 10.4172/2155-6121.s1-005
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Evolution of Airways Hyperresponsiveness and Inflammation

Abstract: Airways hyperresponsiveness (AHR) is usually produced within days of first antigen exposure in mouse models of asthma. Furthermore, continual antigen challenge eventually results in the resolution of the AHR phenotype. Human asthma also waxes and wanes with time, suggesting that studying the time course of AHR in the allergic mouse would offer insights into the variation in symptoms seen in asthmatics. Mice were sensitized with ovalbumin (OVA) on days 0 and 14. As assessed by airway resistance (Rn), lung elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 43 publications
5
48
0
Order By: Relevance
“…OVA/OVA treatment resulted in a pan-pulmonary cellular inflammation in all mice, with participation of both eosinophils (MBP) and neutrophils (MPO). The relatively low number neutrophils relative to eosinophils in the lung of OVA/OVA-treated mice can be ascribed to our treatment protocol, as neutrophils preferentially infiltrate the lung shortly after a challenge (Ͻ24 h) and eosinophils later (43). For the same reason, our relatively extended challenge protocol (6 consecutive days) probably accounts for the observation that only the number of eosinophils corresponded with the functional and biochemical sequels of OVA/OVA treatment (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…OVA/OVA treatment resulted in a pan-pulmonary cellular inflammation in all mice, with participation of both eosinophils (MBP) and neutrophils (MPO). The relatively low number neutrophils relative to eosinophils in the lung of OVA/OVA-treated mice can be ascribed to our treatment protocol, as neutrophils preferentially infiltrate the lung shortly after a challenge (Ͻ24 h) and eosinophils later (43). For the same reason, our relatively extended challenge protocol (6 consecutive days) probably accounts for the observation that only the number of eosinophils corresponded with the functional and biochemical sequels of OVA/OVA treatment (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Although R N was similarly elevated in Glrx1 2/2 animals, increases in tissue resistance and tissue elastance parameters, representing the peripheral airways, were significantly attenuated toward control values ( Figure 6A). Characteristic features of allergic airways disease include excess mucus production and goblet cell hyperplasia (11,14), which have been shown to contribute to airway closure and hyperresponsiveness (15,16). Analysis of the mucin gene, mucin-5AC (Muc5ac), revealed attenuated mRNA expression in the lungs of HDM-exposed Glrx 2/2 mice in comparison to WT mice ( Figure 6B).…”
Section: Assessment Of Hdm-induced Airway Hyperresponsiveness and Mucmentioning
confidence: 99%
“…technique using a computer-controlled small animal ventilator (FlexiVent; SCIREQ, Montreal, PQ, Canada), as previously described (11,12).…”
Section: Assessment Of Airway Hyperresponsivenessmentioning
confidence: 99%
“…It was believed that eosinophils are predominant in asthma, but also the role of neutrophils in asthma is accepted. It has been proved that the majority of the asthmatic patients are noneosinophilic, whereas a direct correlation was reported between neutrophils and severity of asthma [27][28][29][30]. Riesenfeld et al reported variations of phenotypes of AHR in mouse models and believed that a better in understanding of asthma in humans is needed as well.…”
Section: Measurement Diagnosis and Treatmentmentioning
confidence: 99%